Strategy for Managing Generational Differences in The National Police (Polri) - Satria Fauzi Rachmadi; Chairul Muriman Setyabudi; Riska Sri Handayani (Transpublika Publisher, 2025)
This article aims to understand generational differences within the Indonesian National Police (Polri), focusing on work values, communication styles, leadership expectations, technological adaptability, and organizational culture. Using a systematic literature review method, this study identifies unique generational traits of Baby Boomers, Generation X, Generation Y (Millennials), and Generation Z that impact workplace dynamics and collaboration within Polri’s hierarchical structure. The findings reveal that older generations tend to value stability, a strong hierarchy, and directive leadership, while younger generations prioritize flexibility, participatory decision-making, and digital technology. These differences pose challenges to team cohesion but also present opportunities for innovation and enhanced collaboration. To create a harmonious and productive work environment, Polri is recommended to adopt strategies such as hybrid leadership models, cross-generational mentoring programs, and tailored digital training. These efforts are expected to build an inclusive and adaptive organizational culture, enabling Polri to better meet modern law enforcement challenges.